Effects of nitrogen stress and nitrogen form ratios on the bacterial community and diversity in the root surface and rhizosphere of Cunninghamia lanceolata and Schima superba - Wang, Yanru; Li, Xiaoyu; Quan, Xiaoqiang; Liang, Haiyan; Wang, Lidong; Yan, Xiaoli (Frontiers in Plant Science, 2023)
The bacterial communities of root surface and rhizosphere play a crucial role in decomposition and transformation of soil nitrogen (N) and are also affected by soil N levels and distribution, especially the composition and diversity are sensitive to changes in environment with high spatial and temporal heterogeneity of ammonium N (NH4+-N) and nitrate N (NO3--N). One-year-old seedlings of Cunninghamia lanceolata and Schima superba were subjected to N stress (0.5 mmol L-1) and normal N supply (2 mmol L-1), and five different N form ratios (NH4+-N to NO3--N ratio being as 10:0, 0:10, 8:2, 2:8 and 5:5) were created. We analyze the changes in composition and diversity of bacteria in root surface and rhizosphere of two tree species. Differences in the composition of the major bacteria in root surface and rhizosphere of C. lanceolata and S. superba under N stress and N form ratios were not significant. The dominant bacterial phyla shared of two tree species included Proteobacteria and Bacteroidota. Compared to normal N supply, the patterns of diversity in root surface and rhizosphere of two tree species under N stress were distinct for each at five N form ratios. Under N stress, the bacterial diversity in root surface was highest at NH4+-N to NO3--N ratio being 10:0 of C. lanceolata, whereas in root surface was highest at NH4+-N to NO3--N ratio being 0:10 of S. superba. The NH4+-N to NO3--N ratio being 5:5 reduced the bacterial diversity in rhizosphere of two tree species, and the stability of bacterial community in rhizosphere was decreased in C. lanceolata. In addition, the bacterial diversity in root surface was higher than in rhizosphere under N stress of two tree species. Overall, the bacterial compositions were relatively conserved, but diversity changed in root surface and rhizosphere of C. lanceolata and S. superba under N stress and normal N supply. The heterogeneity of ammonium and nitrate N addition should be considered for N-stressed environments to improve bacterial diversity in rhizosphere of two tree species.